DISTRIBUTION OF TETTIGONIOIDEA IN THE FERGANA VALLEY AND INFLUENC-ER FACTORS (Scientific journal of the Fergana State University, 2026)
The article discusses the bioecology and faunal characteristics of the members of the family Orthoptera (Orthoptera: Tettigoniidae) found in the Fergana Valley. The distribution of species in different biotopes in the areas belonging to different natural and agroecosystems of the valley, their ecological adaptation and population dynamics are presented.